Research on Energy Consumption and Energy Saving Measures of Metro Vehicles - Feilong TANG; Qingjun HAN (机车电传动)
Based on the current situation of metro vehicle operation energy consumption, the main components of metro energy consumption from two aspects of traction energy consumption and auxiliary energy consumption were analyzed, as well as the key influencing factors such as signal control vehicle, energy-saving slope and energy-saving power supply in line design. According to the analysis of the current situation of train energy consumption, energy-saving measures were proposed from the aspects of reducing train quality and improving the efficiency of key systems. The energy-saving effects brought by the application of new technologies such as high-frequency auxiliary converter, frequency conversion air-conditioning and intelligent lighting were analyzed, so as to provide reference for energy-saving optimization measures and metro vehicle application selection.